Пособие по математике для поступающих в вузы - Александров Б. И. Борис Иванович; Максимов В. М. Вячеслав Михайлович; Лурье М. В. Михаил Владимирович; Колесниченко А. В. Александр Владимирович (Москва, Изд-во МГУ, 1972)
Исключено из фонда НТБ ТПУ